2010
DOI: 10.1111/j.1365-2095.2010.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on energy budget of Nile tilapia, Oreochromis niloticus

Abstract: A 21-day growth trial was undertaken to investigate the effect of water temperature (25, 28, 31, 34, 37°C) on growth, feed utilization and energy budget of juvenile Nile tilapia (Oreochromis niloticus) (initial body weight around 12 g) with four replicates at each temperature. Feed intake energy (IE), recovered energy (RE), faecal energy (FE), excretory energy (UE + ZE) and heat energy (HE) were calculated to obtain the energy budget. The results showed that feeding rate and ammonia excretion were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
2
22
1
4
Order By: Relevance
“…The energy budget of this study is comparable with those reported for other teleost fish (Fang et al, 2010;Xie et al, 2011). The most similar data set is the energy budget of the Antarctic eelpout, P. brachycephalum, reported by Brodte et al (2006).…”
Section: Energy Budgetsupporting
confidence: 76%
See 1 more Smart Citation
“…The energy budget of this study is comparable with those reported for other teleost fish (Fang et al, 2010;Xie et al, 2011). The most similar data set is the energy budget of the Antarctic eelpout, P. brachycephalum, reported by Brodte et al (2006).…”
Section: Energy Budgetsupporting
confidence: 76%
“…The most similar data set is the energy budget of the Antarctic eelpout, P. brachycephalum, reported by Brodte et al (2006). While routine metabolic costs usually make up about 50% of total energy expenditure in most fish (Brodte et al, 2006;Fang et al, 2010;Xie et al, 2011), the relatively small proportion of energy allocated to routine metabolism (20.8±1.4% at 0°C) in T. bernacchii is noteworthy. Importantly, the measured RMRs in T. bernacchii agree well with recent literature data (Enzor et al, 2013), making an underestimation of metabolic rate seem unlikely.…”
Section: Energy Budgetmentioning
confidence: 87%
“…Diversos autores han reportado que la temperatura del agua es uno de los factores ambientales con mayor impacto en las respuestas fisiológicas de crecimiento y alimentación (Xie, Zheng, Chen, Zhang, Zhu, & Yang, 2011). Kapetsky y Nath (1997) mencionan que la disponibilidad de alimento y la temperatura del agua, parecen ser factores limitantes para el crecimiento de O.niloticus.…”
Section: Discussionunclassified
“…Kapetsky y Nath (1997) mencionan que la disponibilidad de alimento y la temperatura del agua, parecen ser factores limitantes para el crecimiento de O.niloticus. Se han determinado intervalos de mayores crecimientos de O. niloticus en temperaturas de 28 y 32 °C (Likongwe Stecko, Stauffer, & Carline, 1996), 31 a 36 °C (FAO, 2006) y 30.1 °C (Xie et al, 2011). La reducción de la temperatura detiene la reproducción cuando se registran temperaturas de 22 °C.…”
Section: Discussionunclassified
“…The terminology and symbols for the energy budget followed those proposed by the NRC (1981) and Xie et al (2011): The gross energy intake (IE) and fecal energy (FE) were determined directly. The excretory (non-fecal) energy loss is the product of branchial energy (ZE) plus urine energy (UE) and was calculated from the formula: ZE+UE=24.83(NI-NF-Nr) (where NI is gross nitrogen intake, NF is fecal nitrogen, and Nr is recovered nitrogen).…”
Section: Chemical Analysismentioning
confidence: 99%